Biodegradable nanocomposite Fe–Ag load-bearing scaffolds for bone healing. (October 2019) - Sharipova, A.; Gotman, I.; Psakhie, S.G.; Gutmanas, E.Y.
Abstract: Processing and properties of biodegradable load-bearing nanocomposite Fe–Ag scaffolds for bone ingrowth are reported. Fe–Ag nanocomposites were prepared employing high energy attrition milling of powders. Scaffolds with regular interconnected 300–400 μm pores and 60–75% porosity were prepared by cold sintering/high pressure consolidation of nanocomposite Fe–Ag granules, blended with porogen – highly water soluble sugar particles. The scaffolds' strength and permeability were found to be inversely related and to be strongly dependent on porosity. Presence of galvanic nanocouples in Fe5Ag and Fe10Ag resulted in desirable increase of degradation rate in saline solution as compared to pure Fe. The 70% and 75% macroporous Fe–Ag scaffolds possess high compressive strength (9.1–14.9 MPa) and permeability (1.0–3.5·10 −10  m 2 ) being in the range of trabecular/spongy bone. Method of estimation surface area of metal based macroporous scaffolds was proposed and successfully used. Highlights: Load bearing biodegradable FeAg nanocomposite 60–75% porous scaffolds are reported. Nanocomposites were obtained by attrition milling followed by cold sintering. Strength and permeability of 70–75% porous scaffolds - in the range of spongy bone. 4 weeks degradation test results in 61% weight loss on 70% porous Fe5Ag scaffolds. Estimation method of metal scaffold surface area by surface oxidation is proposed.